2009
DOI: 10.1002/ajmg.a.33098
|View full text |Cite
|
Sign up to set email alerts
|

Novel SOX2 mutations and genotype–phenotype correlation in anophthalmia and microphthalmia

Abstract: SOX2 represents a High Mobility Group domain containing transcription factor that is essential for normal development in vertebrates. Mutations in SOX2 are known to result in a spectrum of severe ocular phenotypes in humans, also typically associated with other systemic defects. Ocular phenotypes include anophthalmia/microphthalmia (A/M), optic nerve hypoplasia, ocular coloboma and other eye anomalies. We screened 51 unrelated individuals with A/M and indentified SOX2 mutations in the coding region of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
76
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 30 publications
1
76
1
Order By: Relevance
“…Mutations in the gene for the transcription factor SOX2 result in abnormal development of the brain, eye, gut, and certain craniofacial structures (Kelberman et al, 2006; Zenteno et al, 2006; Schneider et al, 2009). The results of this study indicate that Sox2 HYP mice develop cleft palate at a high penetrance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in the gene for the transcription factor SOX2 result in abnormal development of the brain, eye, gut, and certain craniofacial structures (Kelberman et al, 2006; Zenteno et al, 2006; Schneider et al, 2009). The results of this study indicate that Sox2 HYP mice develop cleft palate at a high penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for the role of SOX2 in human palatal development is provided by the presence of overlapping phenotypes associated with SOX2 haploinsufficiency and the CHARGE association, the latter of which includes cleft palate and is most commonly caused by mutations in the gene that encodes CHD7 (Kelberman et al, 2006; Schneider et al, 2009; Zentner et al, 2010). Notably, CHD7 physically interacts with SOX2 to regulate the expression of other genes that are mutated in several human syndromes (Engelen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous mutations in SOX2 were first reported in patients with bilateral anophthalmia or severe microphthalmia who had additional abnormalities, including developmental delays, learning difficulties, esophageal atresia, and genital abnormalities [9,10,11]. Subsequently, SOX2 mutations were also shown to be associated with anterior pituitary hypoplasia, HH, and variable growth hormone deficiency in association with other manifestations, including hippocampal abnormalities, defects of the corpus callosum, hypothalamic hamartoma, and sensorineural hearing loss [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is a gap in our understanding of how reductions in SOX2 function translate into the morphological defects that are observed in humans with SOX2 haploinsufficiency. This genetic disorder accounts for a significant percentage of cases of anophthalmia, microphthalmia, and coloboma, the latter of which results from a failure of the embryonic optic fissure to fuse (Fantes et al, 2003; Kelberman et al, 2006; Bakrania et al, 2007; Schneider et al, 2009). Previous research using conditional ablation of Sox2 has demonstrated its importance for maintaining the neural potential of retinal progenitors, but the effects of germline Sox2 hypomorphism on the early stages of ocular development have not been defined (Taranova et al, 2006; Matsushima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%